Hubungan Penggunaan Metode Belajar Aktif Tipe Quis Team Terhadap Hasil Belajar Peserta Didik - Nova Enjelia Purba; Hasudungan Simatupang; Rida Gultom (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
The Relationship between the Use of Active Learning Methodes of Quis Team Type and the learning Outcomes of Students in Christian Religius Education and Character Education Class VIII SMP Negeri 4 Tarutung for the 2023/2024 Academic Year” The aim of this research is to determine the positive and significant relationship of using the Quis Team type method on the learning outcomes of students in Christian Education class VIII Negeri 4 Tarutung for the 2023/2024 Academic Year. The method used in this research is a quantitave research method with descriptive and inferential statistical approaches. The population is all class VIII student of SMP Neeri 4 Tarutung for the 2023/2024 academic year, totaling 103 people and sample of 36 people was collected using a positive closed questionnaire with 22 itmes for variable 1) Test the analysis requirements: a) positive relationship tes obtained rxy = 0,567 > rTable (a=0.05,n=36) =0,329. b) Testing a significant relationsip obtained t count = 4,016 > tTable(a=0,05,dk=n-=34) = 2.042. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y=34,36+0,63X. b) Regression coefficient of determination test(r2)= 32,2%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0,05, dk numerator k=11, dk denominator=n-2=36-2=34) namely 16.09 > 2.16. Thus Ha is accepted and Ho is rejected. Thesis: Department of Christian Religius Education, Tarutung State Christian Institute.